2017
DOI: 10.1007/s00572-017-0811-y
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for local adaptation in ectomycorrhizas: a call to track geographical origin of plants, fungi, and soils in experiments

Abstract: Local adaptation, the differential success of genotypes in their native versus foreign environments, can influence ecological and evolutionary processes, yet its importance is difficult to estimate because it has not been widely studied, particularly in the context of interspecific interactions. Interactions between ectomycorrhizal (EM) fungi and their host plants could serve as model system for investigations of local adaptation because they are widespread and affect plant responses to both biotic and abiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…We propose that geography, habitats and methodology should be used more often as covariates in mycorrhizal meta‐studies, as suggested by Rúa et al . ().…”
Section: Problems With the Out Of Context Use Of Mycorrhizal Colonizamentioning
confidence: 97%
“…We propose that geography, habitats and methodology should be used more often as covariates in mycorrhizal meta‐studies, as suggested by Rúa et al . ().…”
Section: Problems With the Out Of Context Use Of Mycorrhizal Colonizamentioning
confidence: 97%
“…A study explicitly incorporating climate, altitude, and soil effects also found that soil fungi mediated the adaptation of Douglas fir seedlings in over half of their treatment combinations (Pickles et al, 2015). However, a recent meta-analysis found no overall effect of host-fungal sympatry on host performance in EM systems, though this conclusion was based on a small number of studies (Rúa et al, 2018).…”
Section: Local Adaptationmentioning
confidence: 99%
“…Clear evidence of the importance of these adaptive processes has been shown for plants forming arbuscular mycorrhizal (AM) symbioses (Rúa et al, 2016a;Johnson et al, 2010), but there have been comparatively few studies exploring local adaptation in ectomycorrhizal (EM) systems. While there is some evidence suggesting the existence of genotype × genotype interactions in ectomycorrhizal hosts (Piculell et al, 2008;Hoeksema & Thompson, 2007;Hoeksema et al, 2012;Pickles et al, 2015); overall, there appears to be little evidence so far for local adaptation in host populations (Rúa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…And although there are notable developments in identifying, surveying and cataloguing the biogeography of fungi (Glassman et al, ; Peay et al, ; Tedersoo et al, ), these attempts lag behind those for plants. One easy solution to this issue would be for researchers to report the geographical origin of plants, fungi and soils used in experiments to enable subsequent meta‐analysis on this topic (Rúa et al, ). Finally, an important finding revealed by quantile regression is that for tree species with small ranges, their response to EM fungal inoculation poorly accounted for the heterogeneity in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Most experiments used fungal mycelia, followed by spores, field soils, and roots to inoculate seedlings. The sources of inoculum were mostly unknown (Rúa et al, ), and the most common growth medium was sand. Most experiments were done in the greenhouse and lasted for approximately 7 months.…”
Section: Methodsmentioning
confidence: 99%